The G-Force conundrum in platelet-rich fibrin generation: Management of a problem hidden in plain sight - Kidambi Sneha; Ajmera Jhansi Rani; Rampalli Viswa Chandra; Sandhya Pavan Kumar; Rajeev Naren Jannu; Srikar Muppirala (Wolters Kluwer Medknow Publications, 2022)
Aim: A force of 400 g at 2700 revolutions per minute (RPM) results in an optimum leukocyte and platelet-rich fibrin (L-PRF). Most of centrifuges with varying characteristics generate a g-force in excess of 700 g at 2700 RPM. In this context, the study explores the effect of the original centrifugation protocol and a modified protocol tailor-made to lower the RPM to generate a g-force of ~ 400 g on platelet concentration, clot size and growth factors release in L-PRF prepared in two different commercially available centrifuges. Materials and Methods: Twenty five subjects each were assigned to the following groups; R1 and R2 where L-PRF was obtained from two laboratory swing-out centrifuges (Remi 8C® and Remi C854®, Mumbai, India), respectively. PRF was obtained from each subject within a group using two protocols; Original (O) protocol: conforming to the original centrifugation cycle (2700 RPM for 12 min) and Modified (M) protocol. Clot size, growth factor estimation, and platelet counts were measured at 20, 40, and 60 min from all the L-PRF clots, respectively. Results: At the third time period (40-60 min), there were no significant differences in clot sizes with the original protocol (P = 0.09), but a highly significant difference was noticed with the modified protocol in both the centrifuges (P = 0.001). Our results showed an increased concentration of vascular endothelial growth factor and epidermal growth factor with modified protocol than with original protocol with both the centrifuges (P = 0.001). By the end of second and third time periods, more platelet concentration was observed with modified protocol than with the original protocol in both the centrifuges (P = 0.001). Conclusion: This study infers that the centrifuge type and relative centrifugal force can affect the quality and quantity of cells and growth factors and an optimum relationship between g-force and RPM should be maintained to obtain L-PRF with adequate cell viability and optimum growth factor release.